Catalytic filter bag for removing dioxin through medium and low temperature denitration as well as preparation method and application of catalytic filter bag

By using a dual-catalyst composition composed of perovskite and ternary talc structures, the risks and low efficiency of amino reducing agents during denitrification in the prior art are solved, and efficient denitrification and dioxin removal effects are achieved at medium and low temperatures.

CN119548904AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411779595.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In the existing waste incineration flue gas purification technology, the denitrification process depends on the amino reducing agent to produce ammonium sulfate and NH3 escape, the operating temperature is high, and the strength of the catalyst and the filter material is not high, resulting in low denitrification and dioxin efficiency.

Method used

A dual catalyst composition, including a catalyst fine powder composed of perovskite and ternary talc structures, is used to form a matrix-supported catalyst sol slurry by mixing with additives and spraying onto a filter bag, thereby achieving medium and low-temperature denitrification and removal of dioxins.

Benefits of technology

Efficient denitrification and dioxin removal are achieved at lower temperatures, avoiding ammonium sulfate generation and NH3 escape problems, improving the binding strength and removal efficiency of catalyst and filter material, and simplifying the process flow.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a catalytic filter bag for removing dioxin through medium and low temperature denitration as well as a preparation method and application of the catalytic filter bag, and belongs to the technical field of waste incineration flue gas purification. The method comprises the following steps: mixing catalyst fine powder and an auxiliary agent, grinding until the particle size is 5-15 microns, uniformly mixing, adding water and a nitric acid solution, and uniformly mixing again, so as to obtain matrix-loaded catalyst sol slurry; and spraying the matrix supported catalyst sol slurry on a pretreated filter bag, and then sequentially drying and roasting to obtain the catalyst filter material. The formed catalyst sol slurry has higher adhesiveness with a filter bag matrix and higher load rate; and an automatic spraying technology is adopted, so that the production efficiency of the catalytic filter bag is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste incineration flue gas purification, and in particular to a catalytic filter bag for removing dioxins by medium- and low-temperature denitration, and a preparation method and application thereof. Technical Background

[0002] Waste incineration flue gas contains multiple pollutants such as NOx, particulate matter, and dioxins, which require different flue gas purification technology combinations for treatment, and there are problems such as complex systems and high costs. The use of flue gas multi-pollutant synergistic removal technology to replace two or more removal technologies in the existing process can effectively simplify the process system and reduce the floor space, thereby reducing the cost of pollutant removal. The catalytic filter bag prepared with dust removal filter material as the basic load coupling SCR denitrification and dioxin removal catalyst can achieve the synergistic and efficient removal of multiple pollutants such as dust, NOx and dioxins.

[0003] There are two main categories of existing catalytic filter bag technologies for dust removal, denitrification and dioxin removal. One is to load vanadium-titanium SCR catalysts on filter bag materials to achieve denitrification and dioxin removal. However, the operating temperature of this type of catalyst exceeds 250°C, which is relatively high and requires relatively high bag material or flue gas temperature. The other is to modify or prepare a denitrification catalyst with a relatively low operating temperature, and then load it on the filter bag material. For example, patent CN104998467A discloses a filter material, which is prepared by mixing a catalyst with PTFE fiber to prepare a catalyst-containing filter material, thereby achieving flue gas denitrification and dioxin removal. Patent CN112717556A discloses a method for preparing a filter material with denitration and dioxin removal functions, wherein high-temperature denitration and dioxin removal catalyst nanoparticles are sprayed onto each layer of the laid net in the stacking process of the traditional needle-punched filter material production process, so that the catalyst nanoparticles use their own heat to partially melt the fiber body after contacting the fiber, and some parts of the nanoparticles are fused with the fiber body and have a certain binding force to form nanoparticle composite fibers, which are then prepared into dust removal filter materials with denitration and dioxin removal functions through processes such as needle punching, singeing, calendering and heat setting. Patent CN 116585885 A discloses a catalytic filter bag with denitration and dioxin removal functions and a preparation method thereof, comprising a breathable membrane layer, a first catalyst composite layer, a second catalyst composite layer and a third catalyst composite layer arranged in sequence from the outside to the inside. Each layer is loaded with a different catalyst. For example, the first catalyst is V2O5-MoO3-CeO2 / TiO2; the second catalyst is a highly efficient synergistic denitrification and dedioxinization catalyst made with cerium dioxide and zirconium oxide as carriers, chromium source, ruthenium source and cobalt source as active precursors, and praseodymium source and molybdenum source as precursors; the third catalyst is V2O5-PdO-Nb2O5 / TiO2 catalyst.

[0004] The above patents mainly have the following problems: first, the denitrification process uses amino reducing agents, such as ammonia water or urea, which poses the risk of ammonium sulfate (and or ammonium bisulfate) generation and NH3 escape; second, the operating temperature is relatively high; third, the preparation process of the catalyst and catalytic filter bag is too complicated and lengthy; fourth, the bonding strength between the catalyst and the filter material is not high, and the denitrification and dioxin removal efficiencies are relatively low. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides a catalytic filter bag for removing dioxins by medium-low temperature denitration and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a catalytic filter bag for removing dioxins by medium-low temperature denitration, the method comprising the following steps:

[0008] (1) Catalyst fine powder: composed of a perovskite-type and a ternary talc-type structure in a weight fraction ratio of 35-65:20-75;

[0009] Wherein, the perovskite is of the general formula RE x Co y Mn z At least one of O3, wherein RE is at least one of La, Ce, Pr and Nd, x = 0 to 0.5, z = 0 to 0.6, y ≤ 1-(x + z);

[0010] The ternary talc-like structure is CuO-NiO-ZrO2; further preferably, the mass ratio of CuO:NiO:ZrO2 in CuO-NiO-ZrO2 is 0.5-2:0.5-2:0.5-2;

[0011] (2) Catalytic filter material: The catalyst fine powder and the additive are mixed and ground to a particle size of 5 to 15 μm, and then water and nitric acid solution are added and mixed again to obtain a matrix-supported catalyst sol slurry;

[0012] (3) The substrate-loaded catalyst sol slurry is sprayed onto the pretreated filter bag, followed by drying and calcining in sequence to obtain the catalyst filter material.

[0013] In the above preparation method, in step (1), RExCo y Mn z The preparation method of the O3 perovskite structure composite is as follows: a metal salt precursor is added to deionized water to dissolve, citric acid is then added and stirred at 60-90°C for 4-8h, the obtained sol is baked at 120-150°C for 6-10h; and finally, the RExCo is obtained after being calcined in a muffle furnace at 580-680°C for 4-8h. yMn z O3 perovskite structure composition;

[0014] Preferred: RExCo y Mn z In the preparation method of the O3 perovskite structure composition: the metal salt precursor RE metal salt precursor, Co metal salt precursor and Mn metal salt precursor; the molar ratio of citric acid to the total metal ions in the metal salt precursor is 1 to 2:1;

[0015] The preparation method of CuO-NiO-ZrO2 is as follows: adding an alcohol solvent to a dodecylamine aqueous solution and stirring the mixture into a microemulsion; adding copper nitrate, nickel nitrate and zirconium nitrate to the microemulsion, adding ammonia water after the mixture is completely dissolved, adjusting the pH value of the solution to 8-10, and then subjecting the solution to hydrothermal crystallization at 120-140°C for 15-28 hours, centrifuging and washing the precipitated product, drying at 110-150°C for 4-8 hours, calcining at 600-700°C for 5-10 hours, and naturally cooling the product to room temperature to obtain a CuO-NiO-ZrO2 ternary talc-like structure composite;

[0016] Preferably: in the preparation method of CuO-NiO-ZrO2, the drying conditions in the preparation method of CuO-NiO-ZrO2 are drying at 110-150°C for 4-8 hours, and the roasting conditions are roasting at 600-700°C for 6-10 hours; the alcohol solvent is n-butanol, and the mass ratio of dodecylamine, water and n-butanol is 1-2:10-20:5-15.

[0017] In the above preparation method, the auxiliary agent described in step (2) is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 5-15:0.1-5; the catalyst fine powder and the auxiliary agent are 1-5:1-5.

[0018] In the above preparation method, the auxiliary agent described in step (2) is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 5-15:0.1-2; the catalyst fine powder and auxiliary agent are 1-3:1-3. :

[0019] In the above preparation method, the mass concentration of the substrate-supported catalyst sol slurry is 1-10%.

[0020] In the above preparation method, the drying temperature in step (3) is 105-115° C., and the drying time is 4-8 hours; the roasting temperature is 150-250° C., and the roasting time is 2-4 hours.

[0021] In the above preparation method, the pretreated filter bag in step (3) is pretreated with 10-30% nitric acid to remove surface impurities, at a temperature of 40-50° C., for 1-3 hours, then washed with deionized water, and dried in a blast drying oven at 100° C. to 110° C. for 1-2 hours to obtain a pretreated filter bag matrix;

[0022] The filter bag matrix is ​​polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS) or polyimide (P84).

[0023] A catalytic filter bag for removing dioxins by medium-low temperature denitration, the catalytic filter bag is prepared by the above method; further, the catalyst loading is 400-600g / m 2 。

[0024] The catalytic filter bag for removing dioxins by medium-low temperature denitration prepared by the above method is used in dust removal, denitration and dioxin removal. The application includes (1) pre-decomposing the methanol catalytic part to form a methanol, H2, CO steam mixture; (2) introducing the steam mixture into the flue gas containing dust, NOx and dioxin waste incineration, removing the smoke dust from the filter bag matrix, and converting NOx and dioxin into N2, H2O and HCl by the catalyst on the filter bag, thereby achieving dust removal, denitration and dioxin removal of the catalytic filter bag.

[0025] Beneficial effects of the present invention: The present invention provides a catalytic filter bag for removing dioxins by medium-low temperature denitration and a preparation method and application thereof. The dual catalyst composition is used as a denitration and dioxin removal catalyst, and has higher denitration and dioxin efficiency at a lower temperature; the non-amino methanol partial decomposition product (methanol, H2, CO steam mixture) is used as a denitration reducing agent, which completely eliminates the generation of ammonium sulfate (or ammonium bisulfate) and the problem of NH3 escape; at the same time, CO is used as a denitration reducing agent and is converted into CO2 during the denitration process without special treatment; ball milling technology is used to make the catalyst and the binder mix more evenly and the particle size smaller, and the formed catalyst sol slurry has stronger adhesion to the filter bag matrix and higher loading rate; automatic spraying technology is used to improve the production efficiency of catalytic filter bags.

[0026] Specific embodiment

[0027] The present invention will be further described below through specific examples, and all examples are operated completely according to the steps described in the present invention.

[0028] Example 1

[0029] (1) Treatment of filter bag substrate

[0030] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0031] (2)La 0.2 Co 0.4 Mn 0.4 Preparation of O3 perovskite structure composites

[0032] 1) Weigh 36.2.3 g La(NO3)3.6H2O (98.5%), 48.4 g Co(NO3)2.6H2O (99.0%) and 42.3 g Mn(NO3)2.4H2O (97.5%) into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0033] 2) Weigh 23.2 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 60° C. for 5 hours to obtain a sol;

[0034] 3) Place the beaker in an oven at 120°C, dry for 8 hours, calcine at 650°C for 6 hours, and cool naturally to room temperature to obtain the La 0.2 Co 0.4 Mn 0.4 O3 perovskite structure composition.

[0035] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0036] 1) Weigh 120.5 g of dodecylamine, dissolve it in 1500 mL of deionized water, add it into a three-necked flask, and start stirring;

[0037] 2) Weigh 1000 mL of n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve dodecylamine in the n-butanol to obtain a microemulsion liquid;

[0038] 3) Weigh 47.3 g Cu(NO3)2.6H2O (98.0%), 99.2 g Ni(NO3)2.6H2O (98.0%) and 39.1 g Zr(NO3)4.3H2O (98.5%) respectively and add them into a three-necked flask;

[0039] 4) When the solid is completely dissolved, add an appropriate amount of ammonia water to adjust the pH to 8.5, and place the liquid in a 5000 ml reactor;

[0040] 5) placing the reactor in an oven at 120° C. for hydrothermal crystallization reaction for 24 hours, centrifuging the product, washing it twice with water, washing it twice with alcohol, drying it at 120° C. for 6 hours, calcining it at 620° C. for 8 hours, and naturally cooling it to room temperature to obtain the CuO-NiO-ZrO ternary talc-like composition of the present invention (weight ratio of CuO:NiO:ZrO2=0.5:1.0:0.5).

[0041] (4) Preparation of substrate-supported catalyst slurry

[0042] Weigh 3.5 g of La obtained in step (2) 0.2 Co 0.4 Mn 0.4 The O3 perovskite composition, 6.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 8.5g of SB powder, and 0.2g of carboxymethyl cellulose are ground and mixed in a ball mill for 4 hours, and the mixture is fully mixed and ground to a particle size of 10μm; 300g of deionized water is added to a 1000mL beaker, and the ball-milled mixture powder is added under stirring, and then 6.5g of 10% nitric acid is slowly added dropwise, and ultrasonic homogenization is performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.75%.

[0043] (5) Preparation of catalytic filter material

[0044] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 4 hours, sprayed three times, and calcined at 200°C for 4 hours to obtain a catalyst loading of 528 g / m 2 Catalytic filter material 1.

[0045] Example 2

[0046] (1) Treatment of filter bag substrate

[0047] Place the polyphenylene sulfide (PPS) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0048] (2) Ce 0.3 Co 0.4 Mn 0.3 Preparation of O3 perovskite structure composites

[0049] 1) Weigh 50.8 g Ce(NO3)3.6H2O (98.5%), 45.1 g Co(NO3)2.6H2O (99.0%) and 29.6 g Mn(NO3)2.4H2O (97.5%) respectively into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0050] 2) Weigh 106.6 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 70° C. for 5 hours to obtain a sol;

[0051] 3) Place the beaker in an oven at 130°C, dry for 7 hours, calcine at 660°C for 8 hours, and cool naturally to room temperature to obtain Ce of the present invention. 0.3 Co 0.4 Mn 0.3 O3 perovskite structure composition.

[0052] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0053] 1) Weigh 120.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, stir until the dodecylamine is completely dissolved in the n-butanol, and obtain a microemulsion liquid; 3) Weigh 54.1g Cu(NO3)2.6H2O (98.0%), 113.4gNi(NO3)2.6H2O (98.0%) and 22.3gZr(NO3)4.3H2O (98.5%) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.0, and the liquid is placed into a 5000ml reactor; 5) the reactor is placed into an oven at 110°C, and the hydrothermal crystallization reaction is carried out for 24 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 125°C for 4 hours, calcined at 650°C for 7 hours, and naturally cooled to room temperature to obtain the CuO-NiO-ZrO ternary talc-like composition of the present invention (weight ratio CuO:NiO:ZrO2=1.0:2.0:0.5).

[0054] (4) Preparation of substrate-supported catalyst slurry

[0055] Weigh 4.5 g of Ce obtained in step (2) 0.3 Co 0.4 Mn 0.3The O3 perovskite structure composition, 2.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 6.5g of SB powder, and 0.2g of carboxymethyl cellulose are ground and mixed in a ball mill for 4 hours, and the mixture is fully mixed and ground to a particle size of 10μm; 300g of deionized water is added to a 1000mL beaker, and the ball-milled mixture powder is added under stirring, and then 5.5g of 10% nitric acid is slowly added dropwise, and ultrasonic homogenization is performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 4.21%.

[0056] (5) Preparation of catalytic filter material

[0057] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed 4 times, and calcined at 180°C for 4 hours to obtain a catalyst loading of 468 g / m 2 Catalytic filter material 2.

[0058] Example 3

[0059] (1) Treatment of filter bag substrate

[0060] Place the polyimide (P84) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0061] (2) Pr 0.5 Co 0.4 Mn 0.1 Preparation of O3 perovskite structure composites

[0062] 1) Weigh 74.9 g Pr(NO3)3.6H2O (98.5%), 37.4 g Co(NO3)2.6H2O (99.0%) and 9.3 g Mn(NO3)2.4H2O (97.5%) into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0063] 2) Weigh 94.0 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 80° C. for 4 hours to obtain a sol;

[0064] 3) Place the beaker in a 140°C oven, dry for 9 hours, calcine at 680°C for 6 hours, and cool naturally to room temperature to obtain the Pr 0.5 Co 0.4 Mn 0.1 O3 perovskite structure composition.

[0065] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0066] 1) Weigh 120.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, stir until the dodecylamine is completely dissolved in the n-butanol, and obtain a microemulsion liquid; 3) Weigh 71.0g Cu(NO3)2.6H2O (98.0%), 74.4gNi(NO3)2.6H2O (98.0%) and 39.1gZr(NO3)4.3H2O (98.5%) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in an oven at 135°C, and the hydrothermal crystallization reaction is carried out for 20 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 110°C for 8 hours, calcined at 680°C for 5 hours, and naturally cooled to room temperature to obtain the CuO-NiO-ZrO ternary talc-like composition of the present invention (weight ratio CuO:NiO:ZrO2=1.5:1.5:1.0).

[0067] (4) Preparation of substrate-supported catalyst slurry

[0068] Weigh 1.5 g of Pr obtained in step (2) 0.5 Co 0.4 Mn 0.1 The O3 perovskite structure composition, 1.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 5.5g of SB powder, and 0.3g of carboxymethyl cellulose are ground and mixed in a ball mill for 3 hours, and the mixture is fully mixed and ground to a particle size of 15μm; 300g of deionized water is added to a 1000mL beaker, and the ball-milled mixture powder is added under stirring, and then 3.5g of 10% nitric acid is slowly added dropwise, and ultrasonic homogenization is performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 2.87%.

[0069] (5) Preparation of catalytic filter material

[0070] The catalyst slurry was coated on the polyimide (P84) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed repeatedly for 5 times, and calcined at 170°C for 4 hours to obtain a catalyst loading of 502 g / m 2 Catalytic filter material 3.

[0071] Example 4

[0072] (1) Treatment of filter bag substrate

[0073] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0074] (2)Nd 0.3 Co 0.3 Mn 0.4 Preparation of O3 perovskite structure composites

[0075] 1) Weigh 50.3 g Nd(NO3)3.6H2O (98.5%), 33.2 g Co(NO3)2.6H2O (99.0%) and 41.6 g Mn(NO3)2.4H2O (97.5%) into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0076] 2) Weigh 107.7 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 80° C. for 6 hours to obtain a sol;

[0077] 3) Place the beaker in a 150°C oven, dry for 6 hours, calcine at 580°C for 8 hours, and cool naturally to room temperature to obtain the Nd 0.3 Co 0.3 Mn 0.4 O3 perovskite structure composition.

[0078] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0079] 1) Weigh 120.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, stir until the dodecylamine is completely dissolved in the n-butanol, and obtain a microemulsion liquid; 3) Weigh 108.2g Cu(NO3)2.6H2O (98.0%), 56.7gNi(NO3)2.6H2O (98.0%) and 22.3gZr(NO3)4.3H2O (98.5%) (weight ratio CuO:NiO:ZrO2=2.0:1.0:0.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 140°C oven, and the hydrothermal crystallization reaction is carried out for 15 hours. The product is centrifuged, washed with water twice, washed with alcohol twice, dried at 130°C for 6 hours, roasted at 700°C for 10 hours, and naturally cooled to room temperature to obtain the CuO-NiO-ZrO ternary talc composition of the present invention.

[0080] (4) Preparation of substrate-supported catalyst slurry

[0081] Weigh 8.5 g of Nd obtained in step (2) 0.3 Co 0.3 Mn 0.4 The O3 perovskite structure composition, 2.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 12.5g of SB powder, and 0.2g of carboxymethyl cellulose are ground and mixed in a ball mill for 6 hours, and the mixture is fully mixed and ground to a particle size of 20μm; 300g of deionized water is added to a 1000mL beaker, and the ball-milled mixture powder is added under stirring, and then 10.5g of 10% nitric acid is slowly added dropwise, and ultrasonic homogenization is performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 7.09%.

[0082] (5) Preparation of catalytic filter material

[0083] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed three times, and calcined at 210°C for 4 hours to obtain a catalyst loading of 573 g / m 2 Catalytic filter material 4.

[0084] Example 5

[0085] (1) Treatment of filter bag substrate

[0086] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0087] (2)La 0.3 Co 0.3 Mn 0.4 Preparation of O3 perovskite structure composites

[0088] 1) Weigh 51.0 g La(NO3)3.6H2O (98.5%), 34.0 g Co(NO3)2.6H2O (99.0%) and 39.7 g Mn(NO3)2.4H2O (97.5%) into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0089] 2) Weigh 107.2 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 90° C. for 6 hours to obtain a sol;

[0090] 3) Place the beaker in an oven at 135°C, dry for 10 hours, calcine at 650°C for 8 hours, and cool naturally to room temperature to obtain the La 0.3 Co 0.3 Mn 0.4 O3 perovskite structure composition.

[0091] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0092] 1) Weigh 120.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, stir to make the dodecylamine completely dissolved in n-butanol, and obtain a microemulsion liquid; 3) Weigh 27.1g Cu(NO3)2.6H2O (98.0%), 113.4gNi(NO3)2.6H2O (98.0%) and 44.6gZr(NO3)4.3H2O (98.5%) (weight ratio CuO:NiO:ZrO2=0.5:2.0:1.0) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.0, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 120°C oven, and the hydrothermal crystallization reaction is carried out for 22 hours. The product is centrifuged, washed with water twice, washed with alcohol twice, dried at 135°C for 6 hours, roasted at 680°C for 8 hours, and naturally cooled to room temperature to obtain the CuO-NiO-ZrO ternary talc-like composition of the present invention.

[0093] (4) Preparation of substrate-supported catalyst slurry

[0094] Weigh 7.0 g of La obtained in step (2) 0.3 Co 0.3 Mn 0.4 The O3 perovskite structure composition, 12.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 12.5g of SB powder, and 0.4g of Tianqing powder were ground and mixed in a ball mill for 4 hours, and the mixture was fully mixed and ground to a particle size of 10μm; 300g of deionized water was added to a 1000mL beaker, and the ball-milled mixture powder was added under stirring, and then 15.5g of 10% nitric acid was slowly added dropwise, and ultrasonic homogenization was performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 9.31%.

[0095] (5) Preparation of catalytic filter material

[0096] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 8 hours, sprayed three times, and calcined at 240°C for 2 hours to obtain a catalyst loading of 586 g / m 2 Catalytic filter material 5.

[0097] Example 6

[0098] (1) Treatment of filter bag substrate

[0099] Place the polyimide (P84) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0100] (2) Ce 0.2 Co 0.3 Mn 0.5 Preparation of O3 perovskite structure composites

[0101] 1) Weigh 36.3 g Ce(NO3)3.6H2O (98.5%), 56.4 g Co(NO3)2.6H2O (99.0%) and 53.0 g Mn(NO3)2.4H2O (97.5%) into a beaker, add 300 mL deionized water, stir and dissolve completely;

[0102] 2) Weigh 114.4 g of citric acid monohydrate (mass percentage concentration ≥ 98.5), add it to the above beaker, and stir vigorously at 90° C. for 6 hours to obtain a sol;

[0103] 3) Place the beaker in an oven at 130°C, dry for 8 hours, calcine at 650°C for 7 hours, and cool naturally to room temperature to obtain Ce of the present invention. 0.2 Co 0.3 Mn 0.5 O3 perovskite structure composition.

[0104] (3) Preparation of CuO-NiO-ZrO ternary talc-like composite

[0105] 1) Weigh 120.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, stir until the dodecylamine is completely dissolved in the n-butanol, and obtain a microemulsion liquid; 3) Weigh 71.0g Cu(NO3)2.6H2O (98.0%), 99.2gNi(NO3)2.6H2O (98.0%) and 19.5gZr(NO3)4.3H2O (98.5%) (weight ratio of CuO:NiO:ZrO2=1.5:2.0:0.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 120°C oven, and the hydrothermal crystallization reaction is carried out for 26 hours. The product is centrifuged, washed with water twice, washed with alcohol twice, dried at 125°C for 6 hours, roasted at 650°C for 8 hours, and naturally cooled to room temperature to obtain the CuO-NiO-ZrO ternary talc-like composition of the present invention.

[0106] (4) Preparation of substrate-supported catalyst slurry

[0107] Weigh 7.0 g of Ce obtained in step (2) 0.2 Co 0.3 Mn 0.5 The O3 perovskite structure composition, 8.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 12.5g of SB powder, and 0.4g of Tianqing powder were ground and mixed in a ball mill for 6 hours, and the mixture was fully mixed and ground to a particle size of 15μm; 300g of deionized water was added to a 1000mL beaker, and the ball-milled mixture powder was added under stirring, and then 12.5g of 10% nitric acid was slowly added dropwise, and ultrasonic homogenization was performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 8.33%.

[0108] (5) Preparation of catalytic filter material

[0109] The catalyst slurry was coated on the polyimide (P84) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 7 hours, sprayed 4 times, and calcined at 175°C for 4 hours to obtain a catalyst loading of 516 g / m 2 Catalytic filter material 6.

[0110] Comparative Example 1

[0111] (1) Treatment of the filter bag substrate and (2) Preparation of the CuO-NiO-ZrO ternary talc-like composition are the same as in Example 1.

[0112] (3) Preparation of substrate-supported catalyst slurry

[0113] Weigh 10.0 g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (3), 8.5 g of SB powder, and 0.2 g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10 μm; add 300 g of deionized water to a 1000 mL beaker, add the ball-milled mixture powder under stirring, and then slowly add 6.5 g of 10% nitric acid dropwise, and ultrasonically homogenize for 8 hours to obtain a matrix-supported catalyst sol slurry with a mass concentration of 5.75%.

[0114] (4) Preparation of catalytic filter material

[0115] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed three times, and calcined at 200°C for 4 hours to obtain a catalyst with a loading of 536 g / m 2 Comparative catalytic filter material 1.

[0116] Comparative Example 2

[0117] (1) Treatment of filter bag substrate and (2) La 0.3 Co 0.3 Mn 0.4 The preparation of the perovskite composition of O3 is the same as in Example 5.

[0118] (3) Preparation of substrate-supported catalyst slurry

[0119] Weigh 19.5g La 0.3 Co 0.3 Mn 0.4 The perovskite composition of O3, 12.5g SB powder and 0.4g Tianqing powder were ground and mixed in a ball mill for 4 hours, and the mixture was fully mixed and ground to a particle size of 10μm; 300g of deionized water was added to a 1000mL beaker, and the ball-milled mixture powder was added under stirring, and then 15.5g of 10% nitric acid was slowly added dropwise, and ultrasonic homogenization was performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 9.31%.

[0120] (4) Preparation of catalytic filter material

[0121] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed three times, and calcined at 240°C for 2 hours to obtain a catalyst loading of 512 g / m 2 Comparative catalytic filter material 2.

[0122] Comparative Example 3

[0123] (1) Treatment of filter bag substrate, (2) La 0.2 Co 0.4 Mn 0.4 The preparation of the perovskite composition of O3 and (3) the preparation of the CuO-NiO-ZrO ternary talc-like composition are exactly the same as the first three steps of Example 1;

[0124] (4) Weigh 3.5 g La 0.2 Co 0.4 Mn 0.4 The perovskite composition of O3, 6.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (2), and 8.7g of carboxymethyl cellulose are ground and mixed in a ball mill for 4 hours. After sufficient mixing and grinding, the particle size reaches 10μm; then 6.5g of 10% nitric acid is slowly added dropwise, and ultrasonic homogenization is performed for 8 hours to obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.75%.

[0125] (5) Preparation of catalytic filter material

[0126] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 7 hours, sprayed three times, and calcined at 160°C for 6 hours to obtain a catalyst loading of 211 g / m 2 Comparative catalytic filter material 3.

[0127] Comparative Example 4

[0128] (1) Treatment of filter bag substrate, (2) Nd 0.3 Co 0.3 Mn 0.4 The preparation of the perovskite composition of O3 and (3) the preparation of the CuO-NiO-ZrO ternary talc-like composition are exactly the same as the first three steps of Example 4;

[0129] (4) Weigh 8.5gNd 0.3 Co 0.3 Mn 0.4 The perovskite composition of O3, 2.5g of the CuO-NiO-ZrO ternary hydrotalcite catalyst composition prepared in step (2), and 12.7g of Tianqing powder were ground and mixed in a ball mill for 6 hours, and the mixture was fully mixed and ground to a particle size of 20μm; 300g of deionized water was added to a 1000mL beaker, and the ball-milled mixture powder was added under stirring, and then 10.5g of 10% nitric acid was slowly added dropwise, and ultrasonic homogenization was performed for 8 hours to obtain a matrix-supported catalyst sol slurry with a mass concentration of 7.09%;

[0130] (5) Preparation of catalytic filter material

[0131] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 8 hours, sprayed three times, and calcined at 210°C for 4 hours to obtain a catalyst loading of 285 g / m 2 Comparative catalytic filter material 4.

[0132] Performance Testing

[0133] The performance evaluation of the catalytic filter bag for removing dioxins by medium and low temperature denitration prepared in the above-mentioned embodiments and comparative examples is carried out by putting the catalytic filter bag on the sleeve. The evaluation conditions are: the NO concentration in the flue gas is 450mg / m 3 , O2 volume fraction is 10%, water vapor content is 15% (volume ratio), SO2 concentration is 350mg / m 3 , dioxin concentration (replaced by chlorobenzene) 10mg / m 3 , dust concentration 2000mg / m 3 , methanol is carried by water vapor into the methanol pre-decomposition bed, the methanol / NO range is 1.05-1.40, the carrier gas is N2, the evaluation temperature range is 140-220℃, the evaluation temperature is 195℃, the methanol / NO is 1.15, and the filtration wind speed is 0.75m / min (filter bag size). The performance of the catalytic filter bag is evaluated by the changes in the inlet and outlet NO, dioxin and dust concentrations. The results are shown in Table 1.

[0134] Table 1 Evaluation of catalytic filter bag denitrification, dedioxin and dust removal performance

[0135] Group Denitrification rate, % Dioxin removal rate, % Dust removal efficiency, % Example 1 99.1 98.6 99.9 Example 2 98.7 98.4 99.7 Example 3 98.6 98.6 98.9 Example 4 99.2 97.8 99.8 Example 5 98.2 98.2 98.5 Example 6 98.7 99.1 99.6 Comparative Example 1 91.2 87.6 99.4 Comparative Example 2 88.5 90.3 98.6 Comparative Example 3 78.8 66.4 98.7 Comparative Example 4 76.4 70.1 99.1

[0136] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A method for preparing a catalytic filter bag for removing dioxins by medium and low temperature denitration, characterized in that: The method comprises the following steps: (1) Catalyst fine powder: composed of a perovskite-type and a ternary talc-type structure in a weight fraction ratio of 35-65:20-75; Wherein, the perovskite is of the general formula RE x Co y Mn z At least one of O3, wherein RE is at least one of La, Ce, Pr and Nd, x = 0 to 0.5, z = 0 to 0.6, y ≤ 1-(x + z); The ternary talc-like structure is CuO-NiO-ZrO2; further preferably, the mass ratio of CuO:NiO:ZrO2 in CuO-NiO-ZrO2 is 0.5-2:0.5-2:0.5-2; (2) Catalytic filter material: The catalyst fine powder and the additive are mixed and ground to a particle size of 5 to 15 μm, and then water and nitric acid solution are added and mixed again to obtain a matrix-supported catalyst sol slurry; (3) The substrate-loaded catalyst sol slurry is sprayed onto the pretreated filter bag, followed by drying and calcining in sequence to obtain the catalyst filter material.

2. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 1, characterized in that: In step (1), RExCo y Mn z The preparation method of the O3 perovskite structure composite is as follows: a metal salt precursor is added to deionized water to dissolve, citric acid is then added and stirred at 60-90°C for 4-8h, the obtained sol is baked at 120-150°C for 6-10h; and finally, the RExCo is obtained after being calcined in a muffle furnace at 580-680°C for 4-8h. y Mn z O3 perovskite structure composition; The preparation method of CuO-NiO-ZrO2 is as follows: adding an alcohol solvent to a dodecylamine aqueous solution and stirring the mixture into a microemulsion; adding copper nitrate, nickel nitrate and zirconium nitrate to the microemulsion, adding ammonia water after they are completely dissolved, adjusting the pH value of the solution to 8-10, and then subjecting the solution to hydrothermal crystallization at 120-140°C for 15-28 hours, centrifuging the precipitated product, washing it, drying it at 110-150°C for 4-8 hours, calcining it at 600-700°C for 5-10 hours, and naturally cooling it to room temperature to obtain a CuO-NiO-ZrO2 ternary talc-like structure composite.

3. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 2, characterized in that: RExD y Mn z In the preparation method of the O3 perovskite structure composition: the metal salt precursor RE metal salt precursor, Co metal salt precursor and Mn metal salt precursor; the molar ratio of citric acid to the total metal ions in the metal salt precursor is 1 to 2:1; In the preparation method of CuO-NiO-ZrO2, the drying conditions in the preparation method of CuO-NiO-ZrO2 are drying at 110-150°C for 4-8 hours, and the roasting conditions are roasting at 600-700°C for 6-10 hours; the alcohol solvent is n-butanol, and the mass ratio of dodecylamine, water and n-butanol is 1-2:10-20:5-15.

4. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 1, characterized in that: The auxiliary agent described in step (2) is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 5-15:0.1-5; the catalyst fine powder and the auxiliary agent are 1-5:1-5.

5. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 5, characterized in that: The auxiliary agent in step (2) is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 5-15:0.1-2; the catalyst fine powder and the auxiliary agent are in a mass ratio of 1-3:1-3.

6. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 1, characterized in that: The mass concentration of the matrix-loaded catalyst sol slurry is 1-10%.

7. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 1, characterized in that: In step (3), the drying temperature is 105-115° C. and the drying time is 4-8 hours; the roasting temperature is 150-250° C. and the roasting time is 2-4 hours.

8. The method for preparing a catalytic filter bag for removing dioxins by medium- and low-temperature denitration according to claim 1, characterized in that: The pretreated filter bag in step (3) is pretreated with 10-30% nitric acid to remove surface impurities at a temperature of 40-50° C. for 1-3 hours, then washed with deionized water, and dried in a blast drying oven at 100° C. to 110° C. for 1-2 hours to obtain a pretreated filter bag matrix; The filter bag matrix is ​​polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS) or polyimide (P84).

9. A catalytic filter bag for removing dioxins by medium and low temperature denitration, characterized in that: The catalytic filter bag is prepared by the method described in any one of claims 1 to 5; further, the catalyst loading is 400 to 600 g / m 2 。 10. Application of the catalytic filter bag for removing dioxins by medium- and low-temperature denitration prepared by the method of claim 1 in dust removal, denitration and dioxin removal.

Citation Information

Patent Citations

  • Filter material with denitration and dioxin-removal effects and preparation method thereof

    CN104998467A

  • Preparation method of filter material with denitration and dioxin removal functions

    CN112717556A

  • Catalytic filter bag with denitration and dioxin removal effects and preparation method thereof

    CN116585885A

  • Method for preparing perovskite-like composite metallic oxide by lamina

    CN101041472A

  • Preparation and application of shell-core-type perovskite-wrapping hydrotalcite-like-based oxide reforming hydrogen production catalyst

    CN103111302A